2024
DOI: 10.1136/bmjgh-2023-014943
|View full text |Cite
|
Sign up to set email alerts
|

“I pity the TB patient”: a mixed methods study assessing the impact of the COVID-19 pandemic on TB services in two major Indonesian cities and distilling lessons for the future

Yusuf Ari Mashuri,
David Boettiger,
Siska Dian Wahyuningtias
et al.

Abstract: IntroductionIn Indonesia, a country with around 280 million people and the second-highest tuberculosis (TB) incidence rate in the world, the impact of the COVID-19 pandemic on TB care needs careful assessment so that future response strategies can be strengthened. We conducted a study comparing TB testing and treatment rates before and during the first 2 years of the COVID-19 pandemic in Indonesia, and the reasons for any disruptions to care.MethodsWe conducted retrospective secondary data analysis and qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…12 Estimates from UNAIDS in 2023 revealed an alarmingly high HIV prevalence among key population groups at higher risk of HIV infection: 13.7% of people who inject drugs; 17.9% of men who have sex with men; 11.9% of transgender individuals; and 2.1% of sex workers. 11 Our study 6 and several other studies [13][14][15][16] have documented the impact of the COVID-19 pandemic on HIV programs and services in Indonesia. In our study, we noted that compared to the pre-pandemic period, individuals living with HIV who visited hospitals had a lower likelihood of starting anti-retroviral treatment (ART), staying in care, and adhering to ART during the pandemic. 17 These disruptions were due, among other things, to social distancing orders, lockdown, and healthcare workers being redeployed to work on COVID-19 testing, contact tracing, and surveillance activities.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…12 Estimates from UNAIDS in 2023 revealed an alarmingly high HIV prevalence among key population groups at higher risk of HIV infection: 13.7% of people who inject drugs; 17.9% of men who have sex with men; 11.9% of transgender individuals; and 2.1% of sex workers. 11 Our study 6 and several other studies [13][14][15][16] have documented the impact of the COVID-19 pandemic on HIV programs and services in Indonesia. In our study, we noted that compared to the pre-pandemic period, individuals living with HIV who visited hospitals had a lower likelihood of starting anti-retroviral treatment (ART), staying in care, and adhering to ART during the pandemic. 17 These disruptions were due, among other things, to social distancing orders, lockdown, and healthcare workers being redeployed to work on COVID-19 testing, contact tracing, and surveillance activities.…”
mentioning
confidence: 58%
“…2 It was also among the top 10 countries that contributed to a global decrease of more than 90% in TB case notifications among people newly diagnosed with TB since 2020, compared with 2019. 2 Further impact of the COVID-19 pandemic on TB services in Indonesia has been documented by our team 6 and others. [7][8][9] We have previously shown that the rates of tuberculosis testing, treatment completion rates, and successful treatment rates decreased in two Indonesian cities (Yogyakarta and Bandung) during the COVID-19 pandemic.…”
mentioning
confidence: 73%
See 2 more Smart Citations